ASSESSMENT OF THE HEALTH AND ECOLOGICAL RISKS CAUSED BY FUNGICIDES IN CHRYSANTHEMUM CULTIVATION BY ENVIRONMENTAL IMPACT QUOTIENT - Thi Thanh Thuan Nguyen; Thi Hang Ho (Tạp chí Khoa học Đại học Đà Lạt)
This study uses the Environmental Impact Quotient (EIQ) to assess the health and ecological risks caused by fungicides used in chrysanthemum cultivation upstream of Xuan Huong Lake, Da Lat city. Survey results reveal that 134 farmers use 21 fungicides with 18 active ingredients on a total area of 35.2 hectares. In all, 18 fungicides with an EIQ at the level of “unlikely to be hazardous” (EIQ < 25) are used on about 95% of the acreage, and 3 fungicides with an EIQ of “slightly hazardous” (25 < EIQ < 50) are used on the rest of the area. The Field Use EIQ of fungicide was rated very low in only 8.2% of the survey area and moderate in 48%. Areas with high and very high ratings account for 3% and 41%, respectively. Using fungicides according to the instructions can reduce the Field Use EIQ values in cultivated areas by 38% and return areas with high and moderate ratings to a low rating. Therefore, it is necessary to instruct farmers on the safe use of fungicides and to recommend those with low EIQ values for chrysanthemum cultivation.